Continuous-Wave Sub-THz Photonic Generation With Ultra-Narrow Linewidth, Ultra-High Resolution, Full Frequency Range Coverage and High Long-Term Frequency Stability - Malzer, Stefan; Criado, Ruben; de Dios, Christina; Preu, Sascha; Prior, E.; Acedo, Pablo; Döhler, Gottfried; Lu, Hong; Gossard, Art (IEEE Transactions on Terahertz Science and Technology, 2013)
We report on a photonic system for generation of high quality continuous-wave (CW) sub-THz signals. The system consists on a gain-switching-based optical frequency comb generator (GS-OFCG), a two-optical-modes selection mechanism and a n-i-pn-i-p superlattice photomixer. As mode selection mechanism, both selective tunable optical filtering using Fabry-Pérot tunable filters (FPTFs) and Optical Injection Locking (OIL) are evaluated. The performance of the reported system surpasses in orders of magnitude the performance of any commercially available optical mm-wave and sub-THz generation system in a great number of parameters. It matches and even overcomes those of the best commercially available electronic THz generation systems. The performance parameters featured by our system are: linewidth 10 Hz at 120 GHz, complete frequency range coverage (60-140 GHz) with a resolution in the order of 0.1 Hz at 120 GHz ( 10 of generated frequency), high long term frequency stability (5 Hz deviation over one hour). Most of these values are limited by the measurement instrumentation accuracy and resolution, thus the actual values of the system could be better than the reported ones. The frequency can be extended straightforwardly up to 1 THz extending the OFCG frequency span. This system is compact, robust, reliable, offers a very high performance, especially suited for sub-THz photonic local oscillators and high resolution spectroscopy.